Antegrade Continence Enema Alone for the Management of Functional Constipation and Segmental Colonic Dysmotility (ACE-FC): A Pediatric Colorectal and Pelvic Learning Consortium Study - Ahmad, Hira; Smith, Caitlin; Witte, Amanda; Lewis, Katelyn; Reeder, Ron William; Garza, Jose; Zobell, Sarah; Hoff, Kathleen; Durham, Megan; Calkins, Casey; Rollins, Michael D.; Ambartsumyan, Lusine; Rentea, Rebecca Maria; Yacob, Desale; Lorenzo, Carlo Di; Levitt, Marc A.; Wood, Richard J. (European Journal of Pediatric Surgery, 2024)
Objective The purpose of the study was to determine if antegrade continence enema (ACE) alone is an effective treatment for patients with severe functional constipation and segmental colonic dysmotility.Methods A retrospective study of patients with functional constipation and segmental colonic dysmotility who underwent ACE as their initial means of management. Data was collected from six participating sites in the Pediatric Colorectal and Pelvic Learning Consortium. Patients who had a colonic resection at the same time as an ACE or previously were excluded from analysis. Only patients who were 21 years old or younger and had at least 1-year follow-up after ACE were included. All patients had segmental colonic dysmotility documented by colonic manometry. Patient characteristics including preoperative colonic and anorectal manometry were summarized, and associations with colonic resection following ACE were evaluated using Fisher's exact test and Wilcoxon rank-sum test. p-Values of less than 0.05 were considered significant. Statistical analyses and summaries were performed using SAS version 9.4 (SAS Institute Inc., Cary, North Carolina, United States).Results A total of 104 patients from 6 institutions were included in the study with an even gender distribution (males n = 50, 48.1%) and a median age of 9.6 years (interquartile range 7.4, 12.8). At 1-year follow-up, 96 patients (92%) were successfully managed with ACE alone and 8 patients (7%) underwent subsequent colonic resection for persistent symptoms. Behavioral disorder, type of bowel management, and the need for botulinum toxin administered to the anal sphincters was not associated with the need for subsequent colonic resection. On anorectal manometry, lack of pelvic floor dyssynergia was significantly associated with the need for subsequent colonic resection; 3/8, 37.5% without pelvic dyssynergia versus 1/8, 12.5% (p = 0.023) with pelvic dyssynergia underwent subsequent colonic resection.Conclusion In patients with severe functional constipation and documented segmental colonic dysmotility, ACE alone is an effective treatment modality at 1-year follow-up. Patients without pelvic floor dyssynergia on anorectal manometry are more likely to receive colonic resection after ACE. The vast majority of such patients can avoid a colonic resection.
Keywords: functional constipation; botulinum toxin; pelvic floor dyssynergia; anorectal manometry; colonic manometry